Cleaning efficacy of a manual toothbrush with tapered filaments - Dörfer, Christof; Bethlenfalvy, Eric von; Bender, Birgit; Pioch, Thomas (Oral health & preventive dentistry, 2003)
To compare the cleaning efficacy of (A): a newly developed manual toothbrush with tapered filaments (meridol®, GABA International, CH-Münchenstein) with (B): a standard flat trim manual toothbrush (ADA reference toothbrush) in vivo.